PELATIHAN PENERAPAN APLIKASI EVALUASI PEMBELAJARAN "STUNNING" BAGI GURU SMAN 1 GEDANGAN, SIDOARJO - Lemantara, Julianto; Effendi, Pradita Maulidya; Prahani, Binar Kurnia; Hariadi, Bambang; Koentjoro, Edo Yonatan (Jurnal Abdimas Bina Bangsa, 2024)
Learning evaluation plays an important role in the teaching and learning process. The learning evaluation process at SMAN 1 Gedangan is still carried out manually, starting from compiling and duplicating questions to assessing and recording learning evaluation results. This requires paper and printing costs. Besides, the process of assessing and recapitulating learning evaluation results takes longer. To overcome this problem, a learning evaluation application called STUNNING was created. However, the implementation of this application needs to be socialized to schools, especially teachers. Therefore, the purpose of this community service activity is to provide training in using the STUNNING application to 15 teachers at SMAN 1 Gedangan so that teachers are skilled in operating it. This training took place twice. The method used was Direct Instruction because it can provide an easier and faster understanding of procedural matters. Training was evaluated by filling out a questionnaire. The questionnaire’s results showed 93.3% of participants thought that overall, this training was very good